Phylogenetic diversity and conservation of crop wild relatives in Colombia - Carlos E. González‐Orozco (Wiley, 2021)
Abstract Crop wild relatives (CWR) are an important agricultural resource as they contain genetic traits not found in cultivated species due to localized adaptation to unique environmental and climatic conditions. Phylogenetic diversity (PD) measures the evolutionary relationship of species using the tree of life. Our knowledge of CWR PD in neotropical regions is in its infancy. We analysed the distribution of CWR PD across Colombia and assessed its conservation status. The areas with the largest concentration of PD were identified as being in the northern part of the central and western Andean mountain ranges and the Pacific region. These centres of high PD were comprised of predominantly short and closely related branches, mostly of species of wild tomatoes and black peppers. In contrast, the CWR PD in the lowland ecosystems of the Amazon and Orinoquia regions had deeply diverging clades predominantly represented by long and distantly related branches (i.e. tuberous roots, grains and cacao). We categorized 50 (52.6%) of the CWR species as ‘high priority’, 36 as ‘medium priority’ and nine as ‘low priority’ for further ex‐situ and in situ conservation actions. New areas of high PD and richness with large ex‐situ gap collections were identified mainly in the northern part of the Andes of Colombia. We found that 56% of the grid cells with the highest PD values were unprotected. These baseline data could be used to create a comprehensive national strategy of CWR conservation in Colombia.